Pentatonic Scale on Electric Guitar as A Mandatory Scale in Music Arts Extracurricular Courses at SMK YPC Tasikmalaya - Al Faridi, Ahmad Fauzi; Wasta, Asep; Apriani, Arni (Riwayat: Educational Journal of History and Humanities, 2024)
This study examines the implementation of the pentatonic scale on electric guitar as a mandatory scale in music extracurricular activities at SMK YPC Tasikmalaya. The research background was based on low levels of student participation and understanding in electric guitar learning. The study employed a qualitative descriptive method with a cross-sectional approach, involving students participating in music extracurricular activities for the 2024/2025 academic year. Data collection was conducted through interviews, observations, documentation, and literature study. The results showed that implementing the pentatonic scale as a mandatory scale had positive impacts, with a 35% increase in improvisation ability and 40% in musical creativity in the experimental group. The program also successfully integrated Indonesian traditional music elements into modern learning, supporting the preservation of local musical culture. The study concludes that implementing the pentatonic scale as a mandatory scale is effective in improving students' technical abilities and musical creativity, while contributing to the development of a comprehensive music learning model at the vocational high school level.